Detoxification of implant surfaces affected by peri-implant disease: an overview of non-surgical methods - Valderrama, Pilar; Blansett, Jonathan A.; Gonzalez, Mayra G.; Cantu, Myrna G.; Wilson, Thomas G. (2014)
Objective: The aim of this review is to summarize the findings of studies that have evaluated non-surgical approaches for detoxification of implant body surfaces in vitro and in vivo, and to evaluate clinical trials on the use of these methodologies for treating peri-implant disease. Materials and methods: A literature search was conducted using MEDLINE (Pubmed) from 1966 to 2013. In vitro and in vivo studies as well as clinical trials on non-surgical therapy were evaluated. The outcome variables were the ability of the therapeutic method to eliminate the biofilm and endotoxins from the implant surface, the changes in clinical parameters including probing depth, clinical attachment levels, bleeding on probing; radiographic bone fill and histological reosseointegration. Results: From 134 a ticles found 35 were analyzed. The findings, advantages and disadvantages of using lasers as well as mechanical and chemical methods are discussed. Most of the in vivo and human studies used combination therapies which makes determining the efficacy of one specific method difficult. Most human studies are case series with short term longitudinal analysis without survival or failure reports. Conclusion: Complete elimination of the biofilms is difficult to achieve using these approaches. All therapies induce changes of the chemical and physical properties of the implant surface. Re-osseointegration may be difficult to achieve if not impossible without surgical access to ensure thorough debridement of the defect and detoxification of the implant surface. Combination protocols for non-surgical treatment of peri-implantitis in humans have shown some positive clinical results but long-term evaluation to evaluate the validity and reliability of the techniques is needed.